2023
DOI: 10.1007/s12015-023-10522-4
|View full text |Cite
|
Sign up to set email alerts
|

Human Amniotic Mesenchymal Stem Cells Alleviate aGVHD after allo-HSCT by Regulating Interactions between Gut Microbiota and Intestinal Immunity

Abstract: Acute graft-versus-host disease (aGVHD) after allogeneic hematopoietic stem cell transplantation poses one of the most vexing challenges. Gut microbiota dysbiosis can proceed aGVHD and mesenchymal stem cells (MSCs) have promising therapeutic potential for aGVHD. However, whether hAMSCs affect the gut microbiota during aGVHD mitigation remains unknown. Accordingly, we sought to define the effects and underlying mechanisms of human amniotic membrane-derived MSCs (hAMSCs) regulating the gut microbiota and intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“… 7 , 42 Understanding the interaction between the intestinal barrier and gut microbiota is essential to maintain the intestinal homeostasis and may promote the advancement of aGVHD treatment. 42 Our recent research has found that hAMSCs may improve aGVHD by regulating the interaction between gut microbiota and intestinal immunity, 12 and therefore, we sought to explore whether overexpressing HLA-G5 in hAMSCs has the same effect on the gut microbiota. Here, we found that the hAMSCs had the capability to repair intestinal barrier damage, as manifested by the increased expressions of ZO-1 and Occludin as well as decreased plasma levels of D-LA and DAO, where these indicators represent the intestinal barrier function and intestinal permeability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 , 42 Understanding the interaction between the intestinal barrier and gut microbiota is essential to maintain the intestinal homeostasis and may promote the advancement of aGVHD treatment. 42 Our recent research has found that hAMSCs may improve aGVHD by regulating the interaction between gut microbiota and intestinal immunity, 12 and therefore, we sought to explore whether overexpressing HLA-G5 in hAMSCs has the same effect on the gut microbiota. Here, we found that the hAMSCs had the capability to repair intestinal barrier damage, as manifested by the increased expressions of ZO-1 and Occludin as well as decreased plasma levels of D-LA and DAO, where these indicators represent the intestinal barrier function and intestinal permeability.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Human amniotic mesenchymal stem cells (hAMSCs) are a type of novel MSCs derived from post-partum placenta, a medical waste, which could be obtained easily, massively and safely without invasive procedures and ethical or moral disputes compared with bone marrow mesenchymal stem cells (BM-MSCs), making them an ideal source of MSCs for GVHD therapy. 10 We have demonstrated that hAMSCs are yet a favorable therapeutic strategy beneficial to aGVHD, 11 and the gut microbiota could be altered after hAMSCs treatment, 12 but the mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%